AUTISM SPECTRUM DISORDER (ASD) TOPIC TRENDS: BIBLIOMETRIC ANALYSIS USING BIBLIOSHINY - Gusti Fawwaz Setyo; Afandi, Afandi; Wahyuni, Eko Sri (Edumedia : Jurnal Keguruan dan Ilmu Pendidikan, 2025)
Bibliometric analysis, a scientific study that uses mathematical and statistical methods to analyze literature, was employed to examine the trends in research on Autism Spectrum Disorder (ASD). The present study utilized data from the Scopus database, which included articles and conference papers published between 2014 and 2023. The study aimed to map and analyze the research direction on ASD. The analysis of 3,879 documents revealed several key findings. Firstly, the topic of ASD exhibited an increasing trend each year. Secondly, certain words such as "autism," "male," and "female" were frequently cited and continued to grow, suggesting emerging research themes. These results provide a comprehensive understanding of the evolving nature of the topic and serve as a valuable foundation for future research and collaboration in health and education. Furthermore, it was observed that research on ASD will continue to expand with diverse research focuses.